Pengembangan Media Pembelajaran Berbantuan Podcast Edukatif Dengan Pendekatan OBE Untuk Meningkatkan Kemampuan Berpikir Kritis - Meiriza, Mica Siar; Sembiring, Ariel Muhammad Jadhi; Lubis, Adelia Marta; Mardiah, Nurul; Simbolon, Legi Likasri (Lembaga Riset dan Inovasi Almatani, 2025)
This research aimed to develop and test the effectiveness of educational podcast-assisted learning media with an Outcome Based Education (OBE) approach in improving students' critical thinking skills in the Neoclassical Economic Thought course. The method employed was Research and Development (R&D) through ten steps according to Sugiyono (2017), involving 32 Economic Education students at Universitas Negeri Medan as subjects. A needs analysis identified key student challenges: difficulty understanding abstract material (mean X1 = 3.17), obstacles due to difficult terminology (mean X3 = 3.17), and the need for flexible media. The educational podcast was developed to offer a communicative audio format capable of simplifying abstract concepts. Feasibility testing by expert validators showed the medium was Very Feasible with an overall average score of 81.1%. Following the intervention using the podcast media, a significant increase in students' critical thinking skills occurred (average score increased from 55.6 on the pretest to 92.1 on the posttest). The effectiveness analysis using the N-Gain test yielded an average value of 0.80, which is classified as High. It is concluded that the OBE-based educational podcast media proved to be Feasible and Effective in enhancing students' critical thinking skills, aligning with the 21 century demands for student-centered and results-oriented learning.